Health econometrics - Baltagi, Badi H. (Badi Hani); Moscone, Francesco (Contributions to economic analysis, 2018)
This volume covers a wide range of existing and emerging topics in applied health economics, including behavioural economics, medical care risk, social insurance, discrete choice models, cost-effectiveness analysis, health and immigration, and more.